FEATURES OF FETAL CRANIAL INJURY DURING THE ANTENATAL PERIOD ACCORDING TO MRT DATA - Kahhorova Feruza Makhmudovna (World Scientific Research Journal, 2025)
Resume: Magnetic resonance imaging (MRT) is a neuroradiological method of choice for diagnosing perinatal lesions of the central nervous system of hypoxic-ischemic type. An important advantage of MRT is the absence of ionizing radiation and The Associated carcinogenesis and absence of mutagenesis effects, which determine the safety of the technique for the mother and fetus. The advantage of MRT over other research methods is due to the objectivity of the data and the presence in the arsenal of diffusion weighted images (DWI) applications, a unique specialized sequence of pulses with a measured diffusion coefficient (CDI). There are few sources of literature with radiological criteria for determining the time of injury of the perinatal central nervous system of hypoxic-ischemic type, and they mainly include descriptions of several cases.